Implementation of bio-inspired optimization algorithms in the System Identification of a FAR 23 aircraft - Agudelo, Daniel; Lichota, Piotr (TECCIENCIA, 2020)
Aircraft aerodynamic forces and moments can be expressed as a function of the dynamic pressure, aircraft dimensions and flight conditions. They are very important do predict the aircraft behavior and performance. Moreover, they play an important role predicting the model response to control inputs. For these reasons it is important to accurate determine the aerodynamic characteristics in terms of stability and control derivatives. This study presents a methodology to precisely estimate stability and control derivatives through system identification procedure. Navion FAR 23 airplane model was used for this purpose. A bio-inspired optimization method was used to create optimal input control signals to excite the model and obtain an output signal with good frequency content that allowed to properly identify the system. Inclusion of bio-inspired methods increased the accuracy of the estimates. The method can be used to identify fixed wing platforms of similar characteristics. Results can be used to develop flight simulators to collect system information regarding certification evidences and to train pilots.